Carbon-atom wires produced by nanosecond pulsed laser deposition in a background gas. (August 2016) - Casari, C.S.; Giannuzzi, C.S.; Russo, V.
Abstract: Wires of sp -hybridized carbon atoms are attracting interest for both fundamental aspects of carbon science and for their appealing functional properties. The synthesis by physical vapor deposition has been reported to provide sp -rich carbon films but still needs to be further developed and understood in detail. Here the synthesis of carbon-atom wires (CAWs) has been achieved by nanosecond pulsed laser deposition (PLD) expoliting the strong out-of-equilibrium conditions occurring when the ablation plasma is confined in a background gas. Surface Enhanced Raman Spectroscopy (SERS) spectra of deposited films indicate that CAWs are mixed with a mainly sp 2 amorphous carbon in a sp-sp 2 hybrid material. Optimal conditions for the deposition of sp -carbon phase have been investigated by changing deposition parameters thus suggesting basic mechanisms of carbon wires formation. Our proof-of-concept may open new perspectives for the targeted fabrication of CAWs and sp-sp 2 structures.